A review of the risk and precipitating factors for spontaneous coronary artery dissection - Stanojevic, Dragana; Apostolovic, Svetlana; Kostic, Tomislav; Mitov, Vladimir; Kutlesic-Kurtovic, Dusanka; Kovacevic, Mila; Stanojevic, Jelena; Milutinovic, Stefan; Beleslin, Branko (Frontiers in Cardiovascular Medicine, 2023)
Introduction. Spontaneous coronary artery dissection (SCAD) is responsible for 1-4% of cases of the acute coronary syndrome (ACS). SCAD is caused by separation within or between any of the three tunics of the coronary artery wall. This leads to intramural hematoma and/or formation of false lumen in the artery, which leads to ischemic changes or infarction of the myocardium. SCAD is more frequent in women compared with men (that ratio is about 9:1). It is estimated that SCAD is responsible for 35% of ACS in women younger than 60 years. The high frequency is noted especially during pregnancy and in peripartum period (first week). In SCAD patients traditional risk factors are rare, except for hypertension. Patients with SCAD have different combination of risk factors compared with patients who have atherosclerotic changes of coronary arteries. We presented the most common associated so called "non-traditional" risk factors in SCAD patients.Risk factors and precipitating disorders which are associated with SCAD. In the literature there are few diseases frequently associated with SCAD and they are marked as predisposing factors. The most common is fibromuscular dysplasia, followed by inherited connective tissue disorders, systemic inflammatory diseases, pregnancy, use of sex hormones or steroids, use of cocaine or amphetamines, thyroid disorders, migraine and tinnitus. In the last few years, genetic predisposition for SCAD is also recognized as predisposing factor. Precipitating factors are also different in women (emotional stress) compared with men (physical stress). Self-reported anxiety and depression are common in women precipitating the SCAD. Those conditions could increase the shear stress to arterial wall and dissection of coronary artery wall. Even after development of SCAD, we can find significant difference in clinical presentation between women and men.In patients with chest pain or other ACS symptoms but with low cardiovascular risk, particularly in female patients, one should suspect that it could be an ACS due to SCAD, particularly in conditions often associated with SCAD. This will increase the recognition of SCAD and timely treatment of those patients.